Pembentukan Nilai-Nilai Religius Pada Keluarga Penerima Manfaat PKH (Program Keluarga Harapan) Di Desa Karangankidul Benjeng Gresik - Eka Qonita; Abdul Mu'id (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2023)
Due to the high level of poverty in Indonesia, the government implemented a program called the "Family Hope Program" as a response to this problem. The program is targeted at low-income or low-income families with special components. One of the long-term goals of this program is to improve Human Resources (HR) in the education sector. This research uses field research methods with a qualitative approach. The data analyzed includes the maintenance of religious values among families who receive the Family Hope Program (PKH), the religious values instilled in families who receive PKH in Karangankidul Benjeng Gresik village, and the impact of PKH on beneficiaries. Participants in this research were PKH recipient families, caregivers, and PKH recipient children. Although the main aim of this program is to instill religious values, this research uses various methods, including observation, interviews, and documentation to collect information. The research results show that religious values are instilled in PKH recipient families through onboarding, role modeling and lecture methods. Apart from that, the religious values conveyed by the PKH coordinator include aspects such as the values of Faith and Taqwa, Gratitude, Devotion, Sincerity, Obedience, Qona'ah, Haya', and trust. Apart from that, Insaniyah values are also a focus, including Silaturahim, Al-Ukhuwah, Al Adl, Husnu-dzan, Al-Tawadlu, Al Wafa, Insyirah, Al-amanah, Qowamiyah, Al-Munfiqun, and Honesty. The impact of the Family Hope Program can be seen in increasing public awareness, especially in the field of education. This is reflected in their ability to remain in school, both in religious schools and public schools.